Determinants of ventricular arrhythmias in human explanted hearts with dilated cardiomyopathy. (18th November 2015) - Parajuli, Nirmal; Valtuille, Lucas; Basu, Ratnadeep; Famulski, Konrad S.; Halloran, Philip F.; Sergi, Consolato; Oudit, Gavin Y.
Abstract: Background: The molecular and cellular determinants of ventricular tachycardia (VT) in patients with nonischaemic dilated cardiomyopathy (NIDCM) remain poorly defined. Materials and methods: We examined 20 NIDCM hearts where VT was reported in 10 cases and VT was absent in 10 cases, using a double‐blinded case–control study design, and assessed the molecular and cellular features of the adverse myocardial remodelling. Results: Explanted hearts from patients with VT showed greater hypertrophic changes based on cardiomyocyte cross‐sectional area and expression of disease markers, and increased myocardial fibrosis which extended into the left ventricular and right ventricular outflow tract regions. The VT group also showed increased oxidative stress with reduction in reduced glutathione levels. Connexin 43 levels in the intercalated discs showed increased levels in the VT group with reduced phosphorylation. Microarray mRNA analysis of gene expression in the left ventricle (LV) free wall revealed several families of genes which were differentially upregulated or downregulated in hearts with documented VT compared to hearts without VT. Notably, we identified reduced expression of the Ca 2+ ‐activated K + channel (KCNN2) and increased expression of the transient receptor potential cation channel 7 (TRPM7) and intracellular chloride channel 3. Western blot analysis on LV membrane fractions showed reduced KCNN2 and increased TRPM7 levels in hearts with VT. Conclusions: In explanted human hearts with NIDCM, VT is associated with greater hypertrophy, oxidative stress and myocardial fibrosis, differential gene expression, and altered ion channel levels indicative of a distinctive adverse myocardial remodelling process associated with clinically significant VT.